2022
DOI: 10.3389/fneur.2022.971399
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular thrombectomy in acute ischemic stroke patients with prestroke disability (mRS ≥2): A systematic review and meta-analysis

Abstract: ObjectiveThe effect of endovascular thrombectomy (EVT) in acute ischemic stroke patients with prestroke disability (modified Rankin Scale score, mRS) ≥2) has not been well-studied. This study aimed to assess the safety and benefit of EVT in patients with prestroke disability.MethodsAccording to PRISMA guidelines, literature searching was performed using PubMed, Embase, and Cochrane databases, for a series of acute ischemic stroke patients with prestroke mRS ≥2 treated by EVT. Random-effects meta-analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, among ACS patients who underwent EVT, it elevated the risk of mortality at 1 year, but was not associated with mortality in PCS. According to a recent meta-analysis of EVT in patients with prestroke disability [7], premorbid disabled patients seem to benefit from EVT. Therefore, as EVT for patients with prestroke disability could be beneficial, cautious selection of EVT candidates is required to enhance stroke prognosis in patients with premorbid functional dependency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among ACS patients who underwent EVT, it elevated the risk of mortality at 1 year, but was not associated with mortality in PCS. According to a recent meta-analysis of EVT in patients with prestroke disability [7], premorbid disabled patients seem to benefit from EVT. Therefore, as EVT for patients with prestroke disability could be beneficial, cautious selection of EVT candidates is required to enhance stroke prognosis in patients with premorbid functional dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Premorbid functional status has been utilized as a strong predictor of post-stroke prognosis, while the premorbid modified Rankin Scale (mRS) has been associated with mortality in acute ischemic stroke patients [4]. Furthermore, as landmark clinical trials that proved the efficacy of endovascular treatment (EVT) only included premorbid-independent patients [5,6], any evidence of the efficacy of EVT in premorbidly dependent patients is not yet supported by clinical trials and has been decided based on clinicians' own decisions [7].…”
Section: Introductionmentioning
confidence: 99%
“…A separate analysis from the same registry [24], looking at 33 patients with high baseline disability (mRS 4–5), reported 84% rate of successful reperfusion and 36% patients returning to baseline functional status. A meta-analysis [25 ▪▪ ] incorporating 13 observational studies and 2625 patients also demonstrated higher likelihood of returning to prestroke functional status (pooled relative risk (RR): 1.86, 95% CI 1.28–2.70) and lower mortality (pooled RR: 0.75, 95% CI 0.58–0.97) when treated with EVT as compared to medical care only. Selection bias remains a concern across these analyses.…”
Section: Lvo Subpopulations Where Endovascular Thrombectomy May Be Co...mentioning
confidence: 92%